MODEL KOMUNIKASI ARSITEKTURALIS SEBAGAI MEDIA DAKWAH - Suharto Suharto (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
This paper deals with the dynamic of the development of technology and information that dominate every public spheres particularly in urban areas today. Modernization of technology plays an important role in determining the development of information and communication either in its capacity as a science or applied science. A myriad of communication models emerge and develop in the phenomenon of communication itself which indicate that modernization of communication is a source of communication technology as applied science. At the same time, modernization of communication using technologies is a part of causing factors to integration of communication compounded with modern architecture. Therefore, it can be used as a medium of Islamic preaching.